Clinical and laboratory characteristics of children with sickle cell disease on hydroxyurea treated with artemether-lumefantrine for acute uncomplicated malaria - Segbefia, Catherine; Amponsah, Seth Kwabena; Afrane, Adwoa K. A.; Nyarko, Mame Yaa; Brew, Yvonne; Salifu, Nihad; Ahorhorlu, Samuel Yao; Sulley, Abdul Malik; Hviid, Lars; Ofori, Michael Fokuo; Adjei, George Obeng (Frontiers in Medicine, 2023)
Introduction Limited information exists on any interactions between hydroxyurea (HU) and antimalarials in sickle cell disease (SCD). We evaluated changes in clinical and laboratory parameters among children with SCD on HU therapy treated with artemether-lumefantrine (AL) for acute uncomplicated malaria (UM). Methods A prospective, non-randomized, pilot study of 127 children with SCD (23, UM; 104, steady state) were recruited from three hospitals in Accra. UM participants were treated with standard doses of AL and followed up, on days 1, 2, 3, 7, 14, and 28. Venous blood was collected at baseline and follow-up days in participants with UM for determination of malaria parasitaemia, full blood count, reticulocytes, and clinical chemistry. Further, Plasmodium falciparum identification of rapid diagnostic test (RDT) positive samples was done using nested polymerase chain reaction (PCR). Results Among SCD participants with UM, admission temperature, neutrophils, alanine-aminotransferase, gamma-glutamyl-transferase, and haemoglobin significantly differed between HU recipients (HU+) and steady state, while white blood cell, neutrophils, reticulocytes, bilirubin, urea, and temperature differed significantly between non-HU recipients (no-HU), and steady state. Mean parasitaemia (HU+, 2930.3 vs. no-HU, 1,060, p = 0.74) and adverse events (HU+, 13.9% vs. no-HU, 14.3%), were comparable (p = 0.94). Day 28 reticulocyte count was higher in the HU+ (0.24) (0.17 to 0.37) vs. no-HU, [0.15 (0.09 to 0.27), p = 0.022]. Significant differences in lymphocyte [HU+ 2.74 95% CI (−5.38 to 58.57) vs. no-HU −0.34 (−3.19 to 4.44), p = 0.024]; bilirubin [HU+, −4.44 (−16.36 to 20.74) vs. no-HU −18.37 (−108.79 to −7.16)]; and alanine aminotransferase, [HU+, −4.00 (−48.55 to 6.00) vs. no-HU, 7.00 (−22.00 to 22.00)] were observed during follow up. Conclusion Parasite clearance and adverse event occurrence were comparable between SCD children treated with AL irrespective of HU status. However, distinct patterns of changes in laboratory indices suggest the need for larger, more focused studies.